Partitioned fluid-structure interaction techniques applied to the mixed-elastohydrodynamic solution of dynamically loaded connecting-rod big-end bearings. (December 2019) - Profito, F.J.; Zachariadis, D.C.; Dini, D.
Abstract: The present contribution proposes different partitioned techniques, which are commonly used in fluid-structure interaction (FSI) applications, in the context of tribological simulations of the transient mixed-elastohydrodynamic problem of dynamically loaded connecting-rod bearings. With the premise that the FSI framework developed is general, in the current work the fluid flow effects have been considered through the averaged Reynolds equation by Patir & Cheng and the mass-conserving p − θ Elrod-Adams cavitation model. The multiphysics simulation framework developed has been used to simulate the connecting-rod big-end bearings of both heavy-duty diesel and high-speed motorcycle engines. In the latter case, the influence of polymer concentration in VM-containing oils with similar HTHS150 values on the bearing power loss is investigated and discussed in details. Highlights: Partitioned FSI methods for solving transient mixed-EHL connecting-rod bearing problems are developed. A simulation framework for journal bearing systems operating under different lubrication regimes is proposed. The influence of polymer concentration in VM-containing engine oils on the frictional performance of high-speed connecting-rod big-end bearings is studied.